2018
DOI: 10.1038/s41467-018-07914-3
|View full text |Cite
|
Sign up to set email alerts
|

Field-level clothianidin exposure affects bumblebees but generally not their pathogens

Abstract: Neonicotinoids are implicated in bee declines and laboratory studies imply that they impair the bee immune system, thereby precipitating a rise in pathogen levels. To establish whether such synergisms reduce bee performance in real-world agricultural landscapes, we analysed the microbial composition of the bumblebee (Bombus terrestris) samples from our recent landscape study on the impacts of field-level clothianidin exposure. We related clothianidin exposure and microbial composition to both individual- and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 70 publications
3
30
1
Order By: Relevance
“…More significantly, exposure to the neonicotinoid thiamethoxam led to a large reduction in queen cell production, with colonies of treatments NFM, NPF, NPM and NPFM producing 40%, 60%, 76% and 72% fewer queen cells than control colonies. These findings are consistent with previous studies that reported a decrease in queen production when bumblebee colonies were exposed to neonicotinoids (Fauser‐Misslin et al., 2014; Rundlöf et al., 2015; Whitehorn et al., 2012; Wintermantel et al., 2018; Woodcock et al., 2017). The fitness of a bumblebee colony is determined by its production of new queens and males (Goulson, 2010), so the fact that colonies exposed to field‐relevant mixtures containing pyrethroids and neonicotinoids, and especially the latter, produced fewer males and queens, may lead to the most serious effects on bumblebees through detrimental consequences at the population level.…”
Section: Discussionsupporting
confidence: 92%
“…More significantly, exposure to the neonicotinoid thiamethoxam led to a large reduction in queen cell production, with colonies of treatments NFM, NPF, NPM and NPFM producing 40%, 60%, 76% and 72% fewer queen cells than control colonies. These findings are consistent with previous studies that reported a decrease in queen production when bumblebee colonies were exposed to neonicotinoids (Fauser‐Misslin et al., 2014; Rundlöf et al., 2015; Whitehorn et al., 2012; Wintermantel et al., 2018; Woodcock et al., 2017). The fitness of a bumblebee colony is determined by its production of new queens and males (Goulson, 2010), so the fact that colonies exposed to field‐relevant mixtures containing pyrethroids and neonicotinoids, and especially the latter, produced fewer males and queens, may lead to the most serious effects on bumblebees through detrimental consequences at the population level.…”
Section: Discussionsupporting
confidence: 92%
“…Another study related to the effects of neonicotinoids on the body in general and intestinal microbiomes in particular, was an experiment with Bombus terrestris [92]. A relationship was found between the effects of clothianidin on the microbial composition of the intestine, both at the individual level and at the colony level.…”
Section: Microbiome Of Bumblebees and Honey Bees And The Impact Of Pementioning
confidence: 99%
“…Hence, for the past two decades, they have been widely used for plant protection and animal health care ( 3 ). However, adverse actions of neonicotinoids on bee behavior, colony size, and queen production have been demonstrated ( 6 13 ). Their intensive use also correlates with reduced numbers of insectivorous birds ( 14 ).…”
mentioning
confidence: 99%